2010
DOI: 10.1681/asn.2008101072
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus-Induced γδ T Cells Associate with Reduced Cancer Risk after Kidney Transplantation

Abstract: An increase in the number of blood ␥␦ T cells follows cytomegalovirus (CMV) infection in kidney transplant recipients. These cells react against CMV-infected cells and tumor epithelial cells in vitro. We hypothesized that these CMV-induced ␥␦ T cells play a protective role against cancer in kidney transplant recipients. We performed a longitudinal case-control study involving 18 recipients who developed cancer between 2 and 6 yr after transplantation and 45 recipients who did not. The median percentage of ␥␦ T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
62
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(66 citation statements)
references
References 35 publications
2
62
0
Order By: Relevance
“…18 Importantly, CMV-induced expansion of Vd2 neg gd T cells correlates with decreased susceptibility to post-transplant cancers, suggesting a role in tumor immunosurveillance in vivo. 19 In line with this, such cells display a TCR-dependent cross-reactivity to several solid tumor cell lines and CMV-infected cells, which can be explained by the recognition of common, specific, stressinduced gd TCR ligands (e.g., EPCR) expressed by cellular targets in both conditions. 18 However, a complex array of co-stimulatory signals along with TCR engagement seem to be required to fine tune appropriate Vd2 neg gd T-cell responses to tissue stress.…”
Section: Introductionmentioning
confidence: 69%
“…18 Importantly, CMV-induced expansion of Vd2 neg gd T cells correlates with decreased susceptibility to post-transplant cancers, suggesting a role in tumor immunosurveillance in vivo. 19 In line with this, such cells display a TCR-dependent cross-reactivity to several solid tumor cell lines and CMV-infected cells, which can be explained by the recognition of common, specific, stressinduced gd TCR ligands (e.g., EPCR) expressed by cellular targets in both conditions. 18 However, a complex array of co-stimulatory signals along with TCR engagement seem to be required to fine tune appropriate Vd2 neg gd T-cell responses to tissue stress.…”
Section: Introductionmentioning
confidence: 69%
“…In the elderly, chronic latent HCMV infection increases the mortality rate, which could be attributed to HCMV-induced immunosenescence with decreased immunity to microbes and cancers (Pawelec et al, 2010;Sansoni et al, 2014;Savva et al, 2013). In the non-elderly, on the other hand, chronic HCMV infection may actually be beneficial in that it augments the T-cell immunity and has been associated with a reduced cancer risk in transplant patients (Couzi et al, 2010;Furman et al, 2015;Pera et al, 2014). In this study, significant intra-tumoural inflammatory responses were more frequently observed in HCMVpositive tumours, suggesting that viral replication may activate the immune response in the tumour microenvironment and contribute to a favourable prognosis (Naito et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The report by Couzi et al 1 also raises some interesting questions. Does the increased number of V␦2 Ϫ ␥␦ T cells demonstrate a direct relationship between CMV infection and immune control of certain tumors?…”
mentioning
confidence: 93%
“…In this issue of JASN, Couzi et al 1 describe a longitudinal case-control study of kidney transplant recipients who developed cancer 2 to 6 years after transplantation. The median percentage of ␥␦ T cells was significantly lower in patients who developed cancer but only in those who had a pre-or posttransplantation cytomegalovirus (CMV) infection.…”
mentioning
confidence: 99%
See 1 more Smart Citation